Peran Kompetensi Guru dalam Meningkatkan Kualitas Pembelajaran Digital di SMP Kota Medan - Pandu Dinata Agustian; Suci Nuraini; Syahputra Ilham; Rafi Ahyar Hasibuan; Tiarnita M. S. Siregar (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the role of the teaching profession in improving the quality of learning in the digital era at the junior high school level in Medan City. The teaching profession encompasses a set of competencies that educators must possess, including pedagogical, personal, social, and professional competencies. In an era of continuous digitalization, the challenges for educators are increasingly complex, requiring ongoing adaptation and competency development. This study employs a qualitative descriptive method with data collection techniques through in-depth interviews, observation, and documentation involving 12 subject teachers from three public junior high schools in Medan City. The results indicate that teachers with high digital literacy are able to create more interactive and student-centered learning environments. Furthermore, the integration of technology in learning has been proven to significantly enhance student motivation and academic outcomes. Challenges encountered include limited technological infrastructure and varying levels of teacher adaptability to change. This study recommends the need for continuous competency-based digital training programs for all educators.